Handbook of research on social software and developing community ontologies - Hatzipanagos, Stylianos, 1963-; Warburton, Steven (Information Science Reference, 2009)
"This book explores how social software and developing community ontologies are challenging the way we operate in a performative space"--Provided by publisher.